Callaway Golf Company and Topgolf : the perfect merger? - Peters, Justin, active 2022; Garon, Jared; Bellaire, Dale A.; Smith, Shaun; Marshall, Derek, active 2022; Dixon, Jess C. (London : Human Kinetics, Inc, 2022)
This case is based on the 2020 merger between Callaway Golf Company, a leader in the golf equipment and apparel industry, and Topgolf Entertainment Group, the top entertainment brand in the golf industry. Mergers have been known to provide greater efﬁciency and proﬁtability, but they can also initiate a clash of corporate cultures, creating conﬂict which may result in a loss of employee satisfaction and brand equity. Along with reviewing the industry and potential outcomes, students will analyze the viability of this merger by conducting a value chain analysis of both companies to look for product alignment. This decision-based case asks students to play the role of Callaway Golf board member Sophia Berckman, who is preparing to make a statement on the prospective merger of the two companies at an emergency board meeting. As such, students will be expected to formulate a recommendation to the board of directors on whether this is a wise business decision using the information provided.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Consolidation and merger of corporations -- Case studies; Valuation -- Case studies